2015 Annual IEEE India Conference (INDICON) 2015
DOI: 10.1109/indicon.2015.7443703
|View full text |Cite
|
Sign up to set email alerts
|

Micro and small-scale HAWT blades airfoils study through CFD for low wind applications

Abstract: In this paper, an analysis of basic airfoils profile for micro and small-scale horizontal axis wind turbine (HAWT) has been studied for different angle-of-attack and fixed Reynolds number. For turbine blade modeling, the data used is from National advisory committee of aeronautics (NACA) of five digit airfoil series. The comprehensive relationship between optimal angle-of-attack and Reynolds number has been analyzed. A low or high lift-to-drag ratio ( / ) can be identified at different angle-of-attack . The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 5 publications
(5 reference statements)
2
9
0
Order By: Relevance
“…One can recognize from this figure that the maximum range for the lift to drag ratio appears to be between 2° and 3.5°. The optimum angle of attack for NACA 63-415 airfoil was previously reported as between 2° and 5.25° (Vendan et al, 2010;Chaudhary and Nayak, 2015). The new result of the present study provides the optimum range for the angle of attack more accurate than the previous literature data.…”
Section: Optimum Angle Of Attacksupporting
confidence: 68%
See 2 more Smart Citations
“…One can recognize from this figure that the maximum range for the lift to drag ratio appears to be between 2° and 3.5°. The optimum angle of attack for NACA 63-415 airfoil was previously reported as between 2° and 5.25° (Vendan et al, 2010;Chaudhary and Nayak, 2015). The new result of the present study provides the optimum range for the angle of attack more accurate than the previous literature data.…”
Section: Optimum Angle Of Attacksupporting
confidence: 68%
“…National Advisory Committee for Aeronautics (NACA) 63-415 airfoil, as one of these turbine blades, has been rarely examined in literature. Additionally, studies in literature have reported inconsistent results where the optimum angle of attack is in the range of 2° to 14° (Vendan et al, 2010;Chaudhary and Nayak, 2015;Yilmaz et al 2016). Therefore, a detailed examination is still necessary for this particular type of the blade to ensure the optimum angle of attack in a precise range.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAWT has rotor angle which functions to rotate the turbine, in order to produce the aerodynamic effect to rotate the rotor, which synchronized with the generator, to produce electrical power. The rotor angle is rotating because of the forces working around it, namely the lift and drag forces [1]. The lift force makes the turbine rotating, while the drag force is the inhibitor force makes the rotating speed of the turbine decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The research work shows that the design angle of attack estimated by numerical simulations were around 2.5% lesser than the experimental techniques. Chaudhary et al [17] conducted aerodynamic analysis on NACA 63415 and NACA 63412 airfoils over a range of angles of attack at Re=1x106 using ANSYS/FLUENT software. Contrastingly, NACA 63415 displayed a better L/D ratio compared to NACA 63412 and recommended to be suitable for the design of rotor blades.…”
Section: Introductionmentioning
confidence: 99%